A solution for future single-electron-counting fast-readout Skipper-CCD experiments: high channel density front-end electronics design and noise performance analysis - Chavez, Claudio; Haro, Miguel Sofo; Lipovetzky, José; Chierchie, Fernando; Fernandez Moroni, Guillermo; Paolini, Eduardo Emilio; Molina, Jorge Luis; Cancelo, Gustavo; Tiffenberg, Javier; Estrada, Juan (SPIE, 2020)
Fil: Chavez, Claudio. Universidad Nacional de Asunción; Paraguay